Religious World-Denying and Trajectories of Activism in the Field of Strongly-Religious Corporative Actors - Olga Michel (Coordinamento SIBA, 2014)
This comparative case study links together the scholarly discourses on religiously-motivated world-rejecting and religious activism. It provides empirical evidence for differentiation between four ideal-typed patterns of religious activism as they relate to different trajectories and spheres of religious world-denying in strongly religious movements: Pattern I (world conquerors) targets inner-worldly sphere of activism in the particular state, using the full scope of political tools to promote its religiously-fueled political agenda. Pattern II (world transformers) creatively combines inner-worldly and other-worldly spheres of activism, applying political strategies in the most advantageous political situations and primarily focusing on strategic missionary activism in “the world.” Pattern III (world creators) utilizes different forms of civic engagement to re-create “the righteous world” on the congregational level, but also participates in missionary activities. Finally, pattern IV (world renouncers) renounces any inner-worldly forms of political or civic engagement as “sinful activity.”